Da trama familiar à escuta do sujeito na clínica psicanalítica da adolescência - Balaban, Alessandra (2009)
The dissertation addresses the psychoanalytic clinic of adolescents from the perspective offered by my practice in a public institution, the Centro de Referência da Infância e Adolescência CRIA [Center of Reference for Childhood and Adolescence]. Similar to the analytic clinical activity with adolescents developed in other settings, many discourses surround the professional in this practice. Parents, teachers, counselors and medical evaluators constitute voices that frequently take part in the search for an adolescent s treatment, as well as in the development of the treatment. Collectively or individually, these voices demand a solution to adolescent s behaviors. Before this knotted scenario, it is up to the professional to hear what the adolescent has to say about what is said about him/her . Thus, when the professional proposes to offer this hearing space, the challenge is related to the fact that the distinction of the actual one who suffers is very blurry. In this work, the view that was adopted was that the adolescent crisis is concerned with an intense psychological work developed by the adolescent in order to move from the family to the social realm. This work is often blocked by a pact of commitment between parents and adolescents, which merited our attention. The analytical work favors the emergence of a crisis different from the one stated by the parents when the adolescent interrogates the position occupied before his/her primordial Others. Such a work points to a rearrangement of the positions occupied during childhood. Anchored in Fundamental Psychopathology and Psychoanalysis, the guidelines for this dissertation are provided by Freudian literature as well as by contemporary works about adolescence